Impact of Insecurity on Students’ Enrolment, Attendance and Retention in Secondary Schools in Katsina State, Nigeria (2017-2022) - Ayinla, Olawuwo Abdulfatai; Belloh, Attiku Muazu; Kankia, Hussaini Adamu (International Journal on Integrated Education, 2023)
This paper reports the outcome of an empirical study on the impact of insecurity on students’ enrolment, attendance and retention in secondary schools in Katsina State, Nigeria from 2017-2022. The problem of insecurity seems affecting students’ enrolment, attendance and retention in various communities in Katsina State and this hinders the realization of the education objectives not only in the State, but the nation at large. The study adopted mixed-research design (a combination of quantitative and qualitative data collection methods).The population of the study was 199 participants comprising of 45 officials of the Ministry of Education in Safana Rimi, Dutsin-ma, Faskari and Kankara Zonal Education Quality Assurance offices), 11 principals, 143 teachers of the post-basic educational institutions in the eleven (11) public junior secondary schools in the affected Local Areas of Katsina State. Multi-stage sampling technique was used for the selection of the study subjects/respondents. The instruments for data collection were a structured questionnaire and document analysis (students’ admission register). The instrument (questionnaire) was validated, pilot tested and the reliability index 0.67 was obtained using Cronbach Alpha technique. Descriptive statistics involving frequency counts and percentage were used for the analysis of respondents’ demographic information, answer to the research questions and students’ admission records. Some of the findings of the study revealed that; the scourge of insecurity in form of banditry, cattle rustling, and abduction constitutes negative impact on students’ enrolment; the plague of insecurity negatively affects students’ attendance; and public junior secondary school students’ retention has been seriously affected as a result of bandits activities in the surveyed Local Government Areas in Katsina State. Therefore, the study made among other recommendation that; the government in collaboration with other relevant stakeholders should make concerted efforts to ensure that adequate security measures be put in place to curtail the menace of insecurity this to enable parents enroll their children to schools and equitable access to education; the government and other relevant stakeholders should vigorously address the issue of insecurity especially in communities located in the rural areas in order for the students have opportunity and access to attend to their daily school activities peacefully; the government and other partnering agencies should continue to appropriate measure to decisively deal with menace of insecurity to ensuring that incident of school close become ‘thing in the past’ in order for the students remain and complete their studies in schools without disruption to academic calendar. This research work will be of significant to policy makers to get an in-depth understanding of insecurity phenomenon and how to manage academic activities amidst of insecurity in secondary schools in the affected areas for.